Morphology and molecular evidence support the validity of Pogonias courbina (Lacepède, 1803) (Teleostei: Sciaenidae), with a redescription and neotype designation - de las Mercedes Azpelicueta, María; Delpiani, Sergio Matías; Cione, Alberto Luis; Oliveira, Claudio [UNESP]; Marceniuk, Alexandre Pires [UNESP]; de Astarloa, Juan Martín Díaz (Public Library of Science (PLoS), 2019)
The family Sciaenidae comprises about 300 species. The black drum Pogonias cromis was the only valid species of the genus. Herein, Pogonias courbina Lacepède 1803 is rede-scribed based on morphological and molecular evidence and a neotype is designated. Pogonias courbina is distinguished by the following characters: the occurrence of characteristic thickening of the dorsal spines VII to XI in all specimens larger than 250 mm SL; all pterygiophores in the dorsal-fin laminar, thin; anal-fin pterygiophores slender excluded those of spines; lateral projections of gas bladder with few finger-like projections; genetic distance between both species 1%; exclusive occurrence of characters in six informative sites of COI (58 G; 214 G; 328 A; 331 A; 553C; 580 G). The method Automatic Barcode gap Discovery detected gaps in nucleotid distance congruent with the NJ, MP, and ML tree analysis. Also, advertisement calls are three times shorter in duration in P. courbina than in P. cromis. In addition, two monophyletic groups for P. cromis and P. courbina appear in trees obtained with different methodologies, emphasizing the absence of shared haplotypes. A gap of about 8000 km occurs in the distribution of both species along coastal areas of the Atlantic Ocean.